Diskresi Dalam Undang-Undang Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan - Muin, Firman (Faculty of Law, Tanjungpura University, 2018)
Discretion raises confusion about jurisdiction in sense of Act No.30 of 2014. Contradiction of discretionary conceptual understanding with discretionary stipulation as a decision and act in accordance with Law admistrtive. Discretion is a concept of free to act, it is not a norm from state administration officers in welfare law (welvaarsstaat). The reason of a great burden of government to obligate creating welfare ( staatbemoienis) in both rush and order ( rush en order) is given discretion. Manisfestation of this is general and abstract policy regulation ( beleid regels), and becomes basic for officials of state administration to create a decision in administrative (beschikking).Â Regulatory policy is as a policy in execution of duty, and a function of service to community examined on the principle of arbitrariness (detournement de pouvoir), magisterial ( willikeur), and the general principle of good governance (algemene beginzelen van behoorlijke bestuur) through administrative appeals or objections. The authorized judiciary obligate to review legitimate or illegitimate policy regulation.